Islamic Republic of Iran : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency for the Islamic Republic of Iran. Since the enactment of the five-year Development Plan covering 2000-04, the authorities have taken a number of steps to enhance fiscal transparency, especially with respect to the budget process. Important recent actions include eliminating implicit exchange rate subsidies, budgetizing other implicit subsidies including those associated with price controls, and adopting contemporary budget classification standards. The audit framework for the public sector has a robust legal framework and follows international auditing standards.